Morpho-physiological and biochemical responses of coconut seedlings in aerated static-solution culture - Yeshashwi Naik, K.; Neenu, S.; Kumar, Dinesh; Ramesh, S. V.; Gopal, Murali; Hebbar, K. B. (Journal of Plantation Crops, 2025)
Coconut (Cocos nucifera L.) is a valuable perennial crop with potential applications in food, feed, and nutraceutical industries. Compared to soil-based cultivation, hydroponic systems offer shorter growing cycles and reduced water waste. This study aimed to analyze the growth of coconut seedlings in hydroponic cultivation systems using Hoagland nutrient solution and water over 1 to 7 months post-germination. Morpho-physiological observations revealed significant differences in total and shoot height, chlorophyll index, stomatal resistance, transpiration rate, and chlorophyll fluorescence traits in seedlings grown in Hoagland nutrient solution compared to those grown in water. Additionally, the leaf area index of seedlings in Hoagland nutrient solution showed a marked increase at 7 and 8 months post-germination, suggesting periodicity in coconut growth and warranting further investigation. Differences in root and shoot nutrient uptake efficiencies were also discussed. This study paves the way for designing effective hydroponic systems for examiningphenology and nutrient dynamics in coconut seedlings.